Boron-containing plastic scintillator and preparation method thereof

By adding inter -carbone or neighbor -carbonized boronum to the plastic flashing body, and using a specific preparation method, the existing plastic flashing body is inadequate when distinguishing the accuracy when distinguishing between neutron and γ -ray signals, realizing efficient efficiency Delivery ability and good physical properties.

CN119351082APending Publication Date: 2025-01-24SICHUAN UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411317332.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing plastic scintillators are insufficiently accurate in distinguishing neutrons from gamma ray signals, and doping with high concentrations of boron-containing compounds and luminescent substances will cause softening, turbidity and yellowing, affecting their performance.

Method used

Use boron -containing plastic flashes, add spa -boronum or adjacent carbon borax, and use inert atmosphere and ultrasonic stirring technology during the preparation process to ensure the high amount and good distribution of light emitting substances, thereby improving its screening ability And physical performance.

Benefits of technology

It achieves efficient thermal neutron-fast neutron-gamma ray discrimination capability, overcomes the problem of insufficient performance of ordinary plastic scintillator, while maintaining good hardness, plasticity and transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351082A_ABST
    Figure CN119351082A_ABST
Patent Text Reader

Abstract

The invention provides a boron-containing plastic scintillator and a preparation method thereof, the boron-containing plastic scintillator comprises the following raw materials by mass: 20%-40% of 2, 5-diphenyloxazole: styrene, 0.1%-0.5% of 7-diethylamino-4-methylcoumarin: styrene, 1%-10% of divinylbenzene: styrene, 0.1%-0.2% of azodiisobutyronitrile: styrene, and the balance of water. The ratio of m-carborane or o-carborane to styrene is 1%-5%. The preparation method comprises the following steps: S1, adding styrene into a container in an inert atmosphere, and introducing inert gas into the container; s2, in an inert atmosphere, adding other raw materials into the container, performing ultrasonic stirring, heating the raw materials in the container to 50 DEG C at the same time, performing heat preservation at 50 DEG C for 72 hours, performing stepped heating for three times to 70 DEG C, performing heat preservation at 70 DEG C for 72 hours, and then performing cooling to room temperature to obtain the boron-containing plastic scintillator. The cross-linking agent is added into the plastic scintillator, so that the plastic scintillator is harder in texture, not prone to deformation, stable and transparent in performance and capable of working normally at the temperature of 60 DEG C, the durability is obviously improved, and the applicable environment is more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of scintillators, and in particular to a boron-containing plastic scintillator and a preparation method thereof. Background Art

[0002] As a commonly used neutron detector, plastic scintillator detectors are widely used in nuclear power generation, nuclear medicine, safety inspection, oil well logging, high energy physics, national defense security, nuclear energy application and other fields. Compared with other inorganic scintillators, plastic scintillators have the advantages of high neutron detection efficiency, fast time response, high counting rate, non-toxicity, non-deliquescent, good radiation resistance, low price, and large-volume preparation. However, due to the coexistence of neutron radiation field and gamma radiation, general plastic scintillator detectors cannot distinguish between neutron and gamma ray signals, which will have a great impact on the accuracy of neutron measurement.

[0003] Plastic scintillators are mainly composed of three parts: substrate, luminescent material, and wave shifter. The principle of plastic scintillator luminescence is that the large π electrons in organic molecules will de-excite and release a large number of photons each time they are excited by ionizing radiation. Each luminescence consists of fast-decaying fluorescence and slow-decaying phosphorescence. The proportion of fluorescence and phosphorescence determines the decay time of each luminescence. The luminescence intensity is proportional to the radiation energy. The photomultiplier device and subsequent circuits convert the collected photons into pulse waveform electrical signals with time and amplitude information.

[0004] Scintillators with pulse shape discrimination (PSD) capabilities are commonly found in liquid scintillators or organic crystals. The principle of pulse shape discrimination (PSD) capabilities is that different types of ionizing radiation have different ionization modes in the scintillator, resulting in different luminescence decay times, and the pulse waveform has different decline rates. Different types of ionizing radiation can be distinguished by distinguishing the pulse decline rates. In order to quantify the quality of the PSD value, a quality factor (Figure Of Merit, FOM) is usually introduced to quantitatively evaluate the separation quality of n-γ discrimination. The FOM factor is the difference between the peak positions of the neutron and γ peaks divided by the sum of the half-height widths of the two peaks:

[0005]

[0006] Where peak n 、peak γ are the central peak positions of the neutron peak and the γ peak of the double Gaussian fitting, respectively, and the FWHM n 、FWHM γThe half-width at half maximum of the neutron peak and the gamma peak respectively. The larger the FOM value, the higher the n-gamma discrimination ability. There are very few means of thermal neutron detection, and detectors containing high thermal neutron cross-section isotopes such as He-3, B-10, and Li-6 are usually used. The higher the content of these isotopes, the higher the thermal neutron detection efficiency of the detector. Plastic scintillators with pulse shape discrimination capabilities require the mass of the luminescent material PPO to account for more than 15%, so that the distance between PPO molecules is close enough to increase the emission of delayed fluorescence. The higher the content of the luminescent material, the better the pulse shape discrimination ability.

[0007] Adding He-3, B-10, Li-6 and other elements to plastic scintillators can make plastic scintillators more efficient in detecting thermal neutrons. However, doping plastic scintillators with high concentrations of boron-containing compounds will cause the plastic scintillators to soften, become turbid and turn yellow. High concentrations of luminescent substances will also cause plastic scintillators to soften, reduce light yield and become turbid, making them unprocessable and unusable. Therefore, the PSD capability of common B-10-doped plastic scintillators is not high, and it is difficult to distinguish the types of incident particles. The main reason is that the concentration of luminescent substances is not high enough, resulting in insufficient discrimination performance, and it is impossible to effectively distinguish thermal neutrons, fast neutrons and gamma events that overlap in the PSD distribution, such as Eljen's EJ-254 plastic scintillator.

[0008] Therefore, preparing a plastic scintillator doped with a sufficient concentration of boron-containing compounds and adding a sufficiently high concentration of luminescent substances is a difficult problem that needs to be solved. Summary of the invention

[0009] The object of the present invention is to provide a boron-containing plastic scintillator, which has a high addition amount of luminescent material and has excellent discrimination ability and good physical properties.

[0010] Another object of the present invention is to provide a method for preparing a boron-containing plastic scintillator. The preparation method is simple and efficient, and the obtained boron-containing plastic scintillator has excellent discrimination ability and good physical properties.

[0011] The present invention solves the technical problem by adopting the following technical solutions.

[0012] In one aspect, a boron-containing plastic scintillator comprises the following raw materials by mass percentage:

[0013] 2,5-diphenyloxazole, 7-diethylamino-4-methylcoumarin, divinylbenzene, azobisisobutyronitrile, m-carborane or o-carborane, styrene; wherein, 2,5-diphenyloxazole: styrene = 20%-40%, 7-diethylamino-4-methylcoumarin: styrene = 0.1%-0.5%, divinylbenzene: styrene = 1%-10%, azobisisobutyronitrile: styrene = 0.1%-0.2%, m-carborane or o-carborane: styrene = 1%-5%.

[0014] Calculated by mass percentage, the raw materials include: 2,5-diphenyloxazole: styrene = 30%, 7-diethylamino-4-methylcoumarin: styrene = 0.2%, divinylbenzene: styrene = 5%; azobisisobutyronitrile: styrene = 0.15%; m-carborane or o-carborane: styrene = 2.5%.

[0015] On the other hand, an embodiment of the present invention provides a method for preparing a boron-containing plastic scintillator, comprising the following steps:

[0016] S1: Under an inert atmosphere, styrene is added into a container, and an inert gas is introduced into the container to discharge oxygen in the styrene;

[0017] S2: Under an inert atmosphere, the remaining raw materials are added into the container, ultrasonically stirred, and the raw materials in the container are heated to 50°C at the same time, then kept at 50°C for 72 hours, then step-wise heated to 70°C for 3 times, and kept at 70°C for 72 hours, and then cooled to room temperature to obtain the boron-containing plastic scintillator.

[0018] In some embodiments of the present invention, in step S2, the three step temperature increases are: uniformly increasing the temperature from 50°C to 55°C within 48 hours; then uniformly increasing the temperature from 55°C to 65°C within 72 hours; then uniformly increasing the temperature from 65°C to 70°C within 72 hours. Styrene and divinylbenzene will generate heat during the polymerization process, and the heat will further catalyze the polymerization, thereby bringing about positive feedback of temperature to trigger violent polymerization, resulting in cracking of the scintillator. Therefore, step temperature increase should be selected during the heating process to make the polymerization process gentle and prevent the scintillator from cracking. After reaching a certain temperature, maintain it for a period of time so that styrene and divinylbenzene can fully complete the polymerization, the structure of each part is uniform, and the physical properties are more stable.

[0019] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0020] The present invention prepares a boron-doped plastic scintillator with high-efficiency thermal neutron-fast neutron-gamma ray discrimination capability. By adding a suitable amount of cross-linking agent, the plastic scintillator has good hardness, plasticity and transmittance, and also greatly increases the solubility of the luminescent substance. By adding m-carborane or o-carborane, a high-efficiency thermal neutron-fast neutron-gamma pulse shape discrimination effect is obtained, and the energy detection range of neutrons and gamma rays that can be discriminated is from tens of keV to several MeV, while still retaining all the advantages of the plastic scintillator. It overcomes the problem that ordinary plastic scintillators do not have the thermal neutron-fast neutron-gamma pulse shape discrimination capability or the thermal neutron-fast neutron-gamma pulse shape discrimination capability is poor. It has a shape discrimination PSD capability that is equivalent to or better than the commercially available EJ-276 plastic scintillator.

[0021] A cross-linking agent is added to the plastic scintillator of the present application, so that the texture of the plastic scintillator becomes harder and less prone to deformation, the performance is stable and transparent, and it can work normally at 60°C. The durability is significantly improved and the applicable environment is expanded. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The plastic scintillator of Example 2-5 is real;

[0024] Figure 2 This is the n-γ discrimination capability resolution diagram of Example 2;

[0025] Figure 3 This is the resolution diagram of EJ254 n-γ discrimination ability;

[0026] Figure 4 The plastic scintillator of Examples 6-10 is real;

[0027] Figure 5 is the thermogravimetric curve of the boron-containing plastic scintillator of Example 5;

[0028] Figure 6 is the displacement-force curve of the plastic scintillator of Examples 1-5 at 60°C;

[0029] Figure 7 1 is the strain-stress curve of the plastic scintillator of Examples 1-5 at 60°C.

[0030] Figure 860° C. displacement-force curves of the plastic scintillators of Examples 6-10;

[0031] Fig. 9 1 is the strain-stress curve of the plastic scintillator of Examples 6-10 at 60°C. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0033] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0034] Examples 1-10

[0035] The raw materials of Example 1-10 are: styrene, PPO (2,5-diphenyloxazole), wave shifter MDAC (7-diethylamino-4-methylcoumarin), initiator AIBN (azobisisobutyronitrile), m-carborane or o-carborane. The proportions of the raw materials of Example 1-9 are shown in Table 1.

[0036] Table 1 Ratios of the raw materials of Examples 1-10

[0037]

[0038]

[0039] The preparation comprises the following steps:

[0040] 1) Vacuum distillation of styrene. In a vacuum environment, use a water bath heating pot to heat the distillation and purification, and the heating temperature is set to 50℃~80℃;

[0041] 2) Pour the styrene obtained in step 1) into an anaerobic bottle and introduce dry nitrogen to deoxygenate for 40 minutes;

[0042] 3) placing the drugs (including the luminescent substance 2,5-diphenyloxazole, the wave shifting agent 7-diethylamino-4-methylcoumarin, the cross-linking agent divinylbenzene, the initiator azobisisobutyronitrile, m-carborane or o-carborane) and the styrene which has been purged with nitrogen in step 2) in sequence into a nitrogen operating environment after loosening the bottle cap;

[0043] 4) Weigh the drugs in a nitrogen environment and bottle them. The mass of the drugs is calculated according to the following standards: Styrene is directly calculated according to the density of styrene based on the size of the plastic scintillator to be made, and the rest of the drugs are added in proportion to the mass of styrene.

[0044] 5) After weighing, mix the drug and the substrate solution, and perform ultrasonic heating to 50°C for prepolymerization. After the prepolymerization, heat in a vacuum environment. During the heating process, the temperature is set as follows: after the initial temperature reaches 50°C, keep it at 50°C for three days, then slowly increase the temperature to 55°C over two days, and then increase the temperature to 65°C and 70°C over three days. After maintaining it at 70°C for three days, you can start cooling it down. Cooling it down to room temperature at a rate of 2°C / h is the best effect.

[0045] 6) Finally, after step 5), the plastic scintillator is taken out of the container, cut and polished to the required size, and then packaged with polytetrafluoroethylene raw tape until only the bottom surface is exposed to prevent atomization.

[0046] Examples 11-14

[0047] The difference from Example 2-5 is that the raw material is replaced with m-carborane, and the remaining raw material ratios and preparation steps are the same.

[0048] Experimental example

[0049] The 90% amplitude of the Compton plateau peak and the relative light yield of the plastic scintillators of Examples 1-5 were tested, and the results are shown in Table 2.

[0050] Table 2 Test results of different crosslinking agents on the flash yield of boron-containing plastics

[0051] Styrene:Divinylbenzene Compton Plateau 50% amplitude (V) Relative light output Example 1 (100:0) 0.302 1 Example 2 (97.5:2.5) 0.27 0.894 Example 3 (95:5) 0.295 0.977 Example 4 (92.5:2.5) 0.258 0.854 Example 5 (90:10) 0.11 0.364

[0052] It can be seen from Table 2 that the performance of the plastic scintillator is improved with the increase of the amount of crosslinking agent. The main reason is that the increase of the amount of crosslinking agent is conducive to the decomposition of micro-region aggregates, forming a smaller microphase structure, making the appearance transparent, but at the same time, with the increase of the amount of crosslinking agent, the physical properties of the plastic scintillator will become more brittle and fragile, so the specific amount needs to be selected at a reasonable value.

[0053] In Example 1, when the cross-linking agent divinylbenzene is not contained in the plastic scintillator substrate, the resulting product is relatively soft and easily deformed by pressure. After the cross-linking agent divinylbenzene is added, the texture becomes significantly harder. At the same time, it can be seen from Table 2 that the volume ratio of styrene to the cross-linking agent divinylbenzene will have a more obvious effect on the relative light yield. Therefore, when adding the cross-linking agent divinylbenzene, it is necessary to select a suitable ratio to add it to ensure that the physical properties of the material are improved without affecting the light yield as much as possible.

[0054] Figure 5 This is the thermogravimetric curve of the boron-containing plastic scintillator of Example 5. The scintillator loses about 25% of its weight at about 235° C. and gradually loses the remaining 75% of its weight at 350° C. to 450° C. It can be seen that the physical properties of this product are improved after adding the crosslinking agent divinylbenzene.

[0055] Figure 6 The displacement-force curve of the plastic scintillator at different crosslinker contents at 60°C. It can be clearly seen from the curve that with the increase of the crosslinker content, the plastic scintillator with a higher crosslinker content can withstand a greater force at the same displacement. At the same time, with the increase of the crosslinker divinylbenzene content, the plastic scintillator will become more brittle, bringing adverse effects.

[0056] Figure 7 The following is the strain-stress curve of the plastic scintillator at different crosslinking agent contents at 60°C. From the curve, it can be seen that when the crosslinking agent divinylbenzene content is higher than 2.5%, the ductility of the plastic scintillator is significantly improved. When the crosslinking agent divinylbenzene content is increased to 10%, the plastic scintillator will gradually become a brittle material and the texture will become more brittle.

[0057] Among them, Figure 6 and Figure 7 0% cross-linking agent is Example 1, 2.5% cross-linking agent is Example 2, in Example 2, the mass ratio of styrene: cross-linking agent = 97.5:2.5; 5% cross-linking agent is Example 3, the mass ratio of styrene: cross-linking agent = 95:5; 7.5% cross-linking agent is Example 4, the mass ratio of styrene: cross-linking agent = 92.5:7.5; 10% cross-linking agent is Example 5, the mass ratio of styrene: cross-linking agent = 90:10.

[0058] The Compton plateau peak position 90% amplitude and relative light yield of the plastic scintillators prepared in Examples 6-9, and the commercially available plastic scintillators EJ299, EJ254, EJ276, and EJ270 from Eljen are shown in Table 3.

[0059] Table 3 Test results of different boron contents on the flash yield of boron-containing plastics

[0060]

[0061] It can be concluded from Table 3 that the plastic scintillators of Examples 6-9 have stable and relatively high light yields, and are all higher than the light yields of plastic scintillators on the market. As the content of the boron-containing compound increases, the relative light yield and the 90% amplitude (V) of the Compton plateau peak position both decrease. The decrease in light yield indicates that the performance of the plastic scintillator decreases, that is, when the boron doping is high, it is difficult for the boron-doped plastic scintillator to have both a high boride content and a high relative light yield. Figure 4From left to right are the plastic scintillators of Examples 6 to 9. As the cross-linking agent of the plastic scintillators increases from left to right, the transparency thereof gradually decreases.

[0062] Figure 2 This is the n-γ discrimination capability resolution diagram (PSD diagram) obtained by double Gaussian fitting in the present invention. The FOM factor obtained by dividing the peak position difference of the neutron and gamma peaks by the sum of the half-height widths of the two peaks can be used to quantitatively evaluate the separation quality of n-γ discrimination. Within a certain range, the larger the FOM factor, the better the discrimination effect; Figure 3 This is the PSD picture of EJ254-254 on the market. Figure 2 and Figure 3 It can be clearly seen that the identification ability of this product has obvious advantages over commercially available products.

[0063] Figure 8 The displacement-force curve of plastic scintillator with different boron contents at 60°C. It can be clearly seen from the curve that with the increase of boron content, the plastic scintillator with higher boron content can withstand less force at the same displacement. At the same time, with the increase of boron content, the plastic scintillator will become more brittle, which will bring adverse effects.

[0064] Fig. 9 The strain-stress curves of plastic scintillators at different boron contents at 60°C. From the curve, it can be seen that when the boron content is lower than 10%, the ductility of the plastic scintillator is significantly improved. When the boron content is increased to 10%, the plastic scintillator will gradually become a brittle material and the texture will become more brittle.

[0065] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A boron-containing plastic scintillator, characterized in that: The invention comprises the following raw materials: 2,5-diphenyloxazole, 7-diethylamino-4-methylcoumarin, divinylbenzene, azobisisobutyronitrile, m-carborane or o-carborane, and styrene; wherein the mass ratio of the raw materials is as follows: 2,5-diphenyloxazole: styrene = 20%-40%, 7-diethylamino-4-methylcoumarin: styrene = 0.1%-0.5%, divinylbenzene: styrene = 1%-10%, azobisisobutyronitrile: styrene = 0.1%-0.2%, and m-carborane or o-carborane: styrene = 1%-5%.

2. The boron-containing plastic scintillator according to claim 1, characterized in that: The mass ratio of each raw material is: 2,5-diphenyloxazole: styrene = 30%, 7-diethylamino-4-methylcoumarin: styrene = 0.2%, divinylbenzene: styrene = 5%; azobisisobutyronitrile: styrene = 0.15%; m-carborane or o-carborane: styrene = 2.5%.

3. A method for preparing a boron-containing plastic scintillator as claimed in claim 1, characterized in that: The following steps are involved: S1: Under an inert atmosphere, styrene is added into a container, and an inert gas is introduced into the container to discharge oxygen in the styrene; S2: Under an inert atmosphere, the remaining raw materials are added into the container, ultrasonically stirred, and the raw materials in the container are heated to 50°C at the same time, then kept at 50°C for 72 hours, then step-wise heated to 70°C for 3 times, and kept at 70°C for 72 hours, and then cooled to room temperature to obtain the boron-containing plastic scintillator.

4. The method for preparing a boron-containing plastic scintillator according to claim 3, characterized in that: In step S2, the temperature is increased three times in steps: uniformly increasing the temperature from 50°C to 55°C within 48 hours; then uniformly increasing the temperature from 55°C to 65°C within 72 hours; then uniformly increasing the temperature from 65°C to 70°C within 72 hours.

5. The boron-containing plastic scintillator according to claim 1, characterized in that: In the step S2, the temperature is lowered to room temperature at a rate of 1°C / h-8°C / h.

Citation Information

Cited By

  • Pure organic carborane-containing X-ray scintillator material and preparation method and application thereof

    CN121555181A

  • A pure organic carbon borane-containing X-ray scintillator material, its preparation method and application

    CN121555181B